2010
DOI: 10.1021/ma902467k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Increase in Seebeck Coefficient and Conductivity in a Doped Poly(alkylthiophene) Blend with Defined Density of States

Abstract: The Seebeck coefficient, a defining parameter for thermoelectric materials, depends on the contributions to conductivity of charge carriers at energies away from the Fermi level. Highly conductive materials tend to exhibit conductivity from carriers close to the Fermi level. In this article, we propose polymer blends in which ground state hole carriers, created by doping a minor additive component, are mainly at an orbital energy set below the hole energy of the major component of the blend. Transport, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 55 publications
7
138
3
2
Order By: Relevance
“…[19][20][21][22][23][24][25] Interest in P3HT as a TE conversion material has increased since 2010. [26][27][28][29] However, the TE properties of pure P3HT are still unsatisfactory at present, with a power factor of o20 μW mK À2 . The poor transport of electrons is caused by the coil conformation and random aggregation of P3HT polymer chains, which is largely due to the flexible hexyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Interest in P3HT as a TE conversion material has increased since 2010. [26][27][28][29] However, the TE properties of pure P3HT are still unsatisfactory at present, with a power factor of o20 μW mK À2 . The poor transport of electrons is caused by the coil conformation and random aggregation of P3HT polymer chains, which is largely due to the flexible hexyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that addition of DIO improves the electrical conductivity and the Seebeck coefficient of PTB7 only in the sample prepared from 1,2,4-trichlorobenzene, while for the samples prepared from chlorobenzene and 1,2-dichlorobenzene, DIO has a negative effect on the thermoelectric properties reflected by the power factor. It is worth noting that both the electrical conductivity and the Seebeck coefficient and therefore, the power factor values of PTB7 samples are higher than some previously reported conducting polymers such as poly [3-hexylthiophene] (P3HT) [13], poly [N-90-heptadecanyl-2,7-carbazole-alt-5,5-(40,70-di-2-thienyl-20,10,3-benzothiadizole)] (PCDTBT) [16], poly carbazolenevinylene derivative, poly paraphenylene, poly p-phenylenevinylene [22] and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) [23]. However, we believe that any changes in chemical structure of the conducting polymers, lead to a modification in their electrical conductivity and influence the thermoelectric effect.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to conventional polymers, conjugated polymers may also be used as thermoelectric materials since they have advantageous characteristics of conventional polymers. The low thermal conductivity, κ, of conjugated polymers (two or three orders of magnitude lower than in inorganic semiconductors) is a major factor when considering conjugated polymers for thermoelectric applications, besides their ease of fabrication via simple solution processability [8,[11][12][13]. The fact that most conducting polymers can be manufactured in the form of thin films over large areas is a potential benefit for multilayered polymer thermoelectric modules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52,53,59] A legnagyobb Seebeck-együtthatókat azonban a vezető polimerek egy másik családja, a poli(3-alkiltiofén)ek (P3AT)k esetén mérték. [60,61] A redukált állapotukban jellemző néhány mV K -1 -es Seebeck-együtthatójú polimerek elektromos vezetése azonban rendkívül kicsi, így ezen polimerek esetében kiemelkedő szerep jut az elektromos vezetés növelésére szolgáló (a következő fejezetekben tárgyalt) eljárásoknak, így a polimer (szupra)molekuláris szerkezeté-nek szabályozásának, illetve a polimer alapú nanokompozitok előállításának.…”
Section: Vezető Polimerek Termoelektromos Tulajdonságaiunclassified